PENGARUH PENERAPAN PERATURAN TENTANG BANGUNAN PADA PEMBENTUKAN APARTEMEN DI KOTA BANDUNG - Alexander Sastrawan; Rumiati R Tobing; Yoza Bona (Research Report - Engineering Science, 2008)
The rapid growingurban demographic influences the housing problem, especially for the healthy and humanize houses.Apartment as one of the vertical housing type become a solution.On the other hand, apartment as a building must fulfilled the administrative criteria and technical criteria which is find in building regulations.Through indepth observation, everybody can see that the building regulations for built up the apartment had not in the appropriate condition. Those situation emerged different interpretation of form and massing apartment’s building.Therefore the aim of this research is to have knowledge abaout the influence of building regulations in buiding process of apartment.This research had choosen an apartment building named Dagobutik, which is located in north Bandung as the case study. Investegated and identified through the building regulations which are positive using in Bandung as local government building laws.